(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
The article analyzes the specific features of the use of some unconventional methods in foreign countries in investigating crimes, and studies the application of one of these methods in the practice of Uzbekistan in exposing the crime of staged murder using a polygraph.